Health assessment in nursing - Weber, Janet R.; Kellley, Jane H. (Philadelphia, Pennsylvania : Wolters Kluwer, 2022)
Clearly written, colorfully designed, and updated with the most current, evidence-based nursing considerations, Health Assessment in Nursing, 7th Edition helps students develop the comprehensive knowledge base and expert nursing assessment skills to confidently perform accurate, timely health assessments in a variety of healthcare settings.
UNIT 1 Nursing Data Collection, Documentation, and Analysis -- Chapter 1 The Nurse's Role in Health Assessment -- Chapter 2 Collecting Subjective Data: The Interview and Health History -- Chapter 3 Collecting Objective Data: The Physical Examination -- Chapter 4 Validating and Documenting Data -- Chapter 5 Thinking Critically to Analyze Data to Make Informed Clinical Judgments -- UNIT 2 Integrative Holistic Nursing Assessment -- Chapter 6 Assessing Mental Status Including Risk for Substance Abuse -- Chapter 7 Assessing Psychosocial, Cognitive, and Moral Development -- Chapter 8 Assessing General Health Status and Vital Signs -- Chapter 9 Assessing Pain -- Chapter 10 Assessing for Violence -- Chapter 11 Assessing Culture -- Chapter 12 Assessing Spirituality and Religious Practices -- Chapter 13 Assessing Nutritional Status -- UNIT 3 Nursing Assessment of Physical Systems -- Chapter 14 Assessing Skin, Hair, and Nails -- Chapter 15 Assessing Head and Neck -- Chapter 16 Assessing Eyes -- Chapter 17 Assessing Ears -- Chapter 18 Assessing Mouth, Throat, Nose, and Sinuses -- Chapter 19 Assessing Thorax and Lungs -- Chapter 20 Assessing Breasts and Lymphatic System -- Chapter 21 Assessing Heart and Neck Vessels -- Chapter 22 Assessing Peripheral Vascular System -- Chapter 23 Assessing Abdomen -- Chapter 24 Assessing Musculoskeletal System -- Chapter 25 Assessing Neurologic System -- Chapter 26 Assessing Male Genitalia and Rectum -- Chapter 27 Assessing Female Genitalia, Anus, and Rectum -- Chapter 28 Pulling It All Together: Integrated Head-To-Toe Assessment -- UNIT 4 Nursing Assessment of Special Groups -- Chapter 29 Assessing Childbearing Women -- Chapter 30 Assessing Newborns and Infants -- Chapter 31 Assessing Children and Adolescents -- Chapter 32 Assessing Older Adults -- Chapter 33 Assessing Families -- Chapter 34 Assessing Communities -- Appendix A Nursing History Guide -- Appendix B Physical Assessment Guide -- Appendix C Manual of Collaborative Problems.
Includes index.
Keywords: NURSING